Religious development for convicts: a study in Pangkalan Berandan prison, Babalan regency - Karo-Karo, Desy Nuryani; Daulay, Nurussakinah; Al Farabi, Mohammad (Universitas Pendidikan Indonesia, 2023)
This study aims to analyze the religious guidance program for prisoners used in Class II B Prison in Pangkalan Berandan, Babalan Regency. To what extent can the results of this spiritual guidance affect the personality of the prisoner in Class II B Prison in Pangkalan Berandan. This research is qualitative in the form of an analytical description. This research data was collected by the method; 1) Observation, 2) Interview, and 3) Document Study. The results of this study indicate that: 1) There are three development programs implemented in Class II B Prison Pangkalan Berandan, Babalan district, namely spiritual development, independence development, and development of national and state awareness. 2) The implementation of religious guidance for convicts is carried out by (permanent) Islamic religious advisors and also prison staff (as a substitute for and monitors convicts). The implementation of the guidance carried out by the Islamic Religious Advisors uses the lecture method (tausiyah), questions and answers, practice, and memorization. 3) The implementation of Islamic spiritual development shows significant results, especially those related to worship, such as prayer, memorizing short verses, and others.Penelitian ini bertujuan untuk menganalisis program bimbingan agama bagi narapidana yang digunakan di Lapas Kelas II B Pangkalan Berandan Kabupaten Babalan. Sejauh mana hasil bimbingan spiritual tersebut dapat mempengaruhi kepribadian narapidana di Lapas Kelas II B Pangkalan Berandan. Penelitian ini bersifat kualitatif dengan bentuk deskripsi analitis. Data penelitian ini dikumpulkan dengan metode; 1) Observasi, 2) Wawancara, dan 3) Studi Dokumen. Hasil penelitian ini menunjukkan bahwa: 1) Terdapat tiga program pengembangan yang dilaksanakan di Lapas Kelas II B Pangkalan Berandan kecamatan Babalan yaitu pengembangan spiritual, pengembangan kemandirian, dan pengembangan kesadaran berbangsa dan bernegara. 2) Pelaksanaan bimbingan keagamaan bagi narapidana dilakukan oleh penasihat agama Islam (tetap) dan juga petugas penjara (sebagai pengganti dan pengawas narapidana). Pelaksanaan bimbingan yang dilakukan oleh Pembimbing Agama Islam menggunakan metode ceramah (tausiyah), tanya jawab, praktek, dan hafalan. 3) Implementasi pengembangan spiritual Islam menunjukkan hasil yang signifikan terutama yang berkaitan dengan ibadah, seperti shalat, hafalan ayat pendek, dan lain-lain.